2011
DOI: 10.1111/j.1476-5381.2011.01499.x
|View full text |Cite
|
Sign up to set email alerts
|

Mephedrone, compared with MDMA (ecstasy) and amphetamine, rapidly increases both dopamine and 5-HT levels in nucleus accumbens of awake rats

Abstract: BACKGROUND AND PURPOSEThe designer drug 1-(4-methylphenyl)-2-methylaminopropan-1-one (4-methylmethcathinone, mephedrone) is reported to possess psychostimulant, entactogenic and hallucinogenic effects. The purpose of this study was to examine the effects of acute administration of mephedrone on extracellular levels of dopamine (DA) and 5-HT in the nucleus accumbens of awake rats and compare these effects with those induced by 3,4-methylenedioxymethamphetamine (MDMA, ecstasy) and amphetamine. EXPERIMENTAL APPRO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

34
229
4
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(272 citation statements)
references
References 50 publications
34
229
4
5
Order By: Relevance
“…It increases extracellular dopamine and to an even greater extent 5-HT in the nucleus accumbens (Baumann et al, 2012;Eshleman et al, 2013;Kehr et al, 2011;Wright et al, 2012). The current study, in contrast, suggests that in the striatum, the percentage increase in 5-HT and dopamine is rather similar, at least after the second and third injections.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…It increases extracellular dopamine and to an even greater extent 5-HT in the nucleus accumbens (Baumann et al, 2012;Eshleman et al, 2013;Kehr et al, 2011;Wright et al, 2012). The current study, in contrast, suggests that in the striatum, the percentage increase in 5-HT and dopamine is rather similar, at least after the second and third injections.…”
Section: Discussioncontrasting
confidence: 51%
“…Once transported into the cell mephedrone stimulates neurotransmitter release and disrupts vesicular storage by interaction with the vesicular monoamine transporter (VMAT) and can also stimulate non-exocytotic release by reversing the monoamine transporter flux (Simmler et al, 2013). Consistent with this, systemic mephedrone administration to freely moving rats elevates extracellular levels of dopamine, and to a greater extent 5-HT, in the nucleus accumbens (Baumann et al, 2012;Kehr et al, 2011;Wright et al, 2012).…”
Section: Introductionsupporting
confidence: 50%
See 1 more Smart Citation
“…There are notable differences in transporter selectivity across this group of compounds as well. Mephedrone and methylone are non-selective transporter substrates that produce neurochemical effects akin to those produced by MDMA (Baumann et al, 2012;Kehr et al, 2011). By contrast, MDPV is a catecholamine-selective uptake blocker.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in animal models indicate that mephedrone acts as a monoamine releaser and a reuptake inhibitor (Simmler et al, 2013;Baumann et al, 2012;López-Arnau et al, 2012). It has, therefore, been shown to increase dopamine in a similar manner to amphetamine and produce more serotonin increase (5-HT) than MDMA (Baumann et al, 2012;Kehr et al, 2011). The profile of mephedrone action on monoamine receptors and transporters suggests it could have a high abuse liability, and several studies have found that it supports self-administration at a higher rate than MDMA (Green et al, 2014).…”
Section: Introductionmentioning
confidence: 99%